Spanish Version of the Scale "Eventos Adversos Associados às Práticas de Enfermagem" (EAAPE): Validation in Nursing Students - Antonio Martínez-Sabater; Carlos Saus-Ortega; Mónica Masiá-Navalon; Elena Chover-Sierra; María Luisa Ballestar-Tarín (MDPI AG, 2022)
Healthcare carried out by different health professionals, including nurses, implies the possible appearance of adverse events that affect the safety of the patient and may cause damage to the patient. In clinical practice, it is necessary to have measurement instruments that allow for the evaluation of the presence of these types of events in order to prevent them. This study aims to validate the "Eventos adversos associados às práticas de enfermagem" (EAAPE) scale in Spanish and evaluate its reliability. The validation was carried out through a cross-sectional study with a sample of 337 nursing students from the University of Valencia recruited during the 2018-19 academic year. An exploratory factor analysis was carried out using principal components and varimax rotation. The factor analysis extracted two factors that explained 32.10% of the total variance. Factor 1 explains 22.19% and refers to the "adverse results" of clinical practice (29 items), and factor 2 explains 9.62% and refers to "preventive practices" (24 items). Both factors presented high reliability (Cronbach's alpha 0.902 and 0.905, respectively). The Spanish version of the EAAPE is valid and reliable for measuring the perception of adverse events associated with nursing practice and the presence of prevention measures.